Septic Shock Caused by Aeromonas veronii in a Patient with Chronic Liver Disease: a Case Report - Lopes, Débora; Neto Real, André; Catorze, Nuno (Brazilian Journal of Case Reports, 2024)
Aeromonas species are gram-negative bacilli found in freshwater or brackish water. This infection is acquired in the community through the consumption of contaminated water and food, as well as through traumatic wounds in contact with contaminated soil or water. A 44-year-old man, with a history of chronic liver disease and significant alcohol consumption, was brought to the Emergency Department (ED) with complaints of nausea and food-related vomiting, associated with jaundice, fever, and night sweats for 5-6 days, as well as epistaxis. He denied other complaints. A few days prior, he had gone fishing and, on physical examination, presented with multiple cuts on both feet. Laboratory tests revealed hematological, renal, and hepatic dysfunction. Microbiological screening showed positive blood and urine cultures for Aeromonas veronii. The patient was admitted to the Intensive Care Unit (ICU) with septic shock and multiorgan dysfunction, progressing to refractory septic shock, and eventually passed away. Aeromonas veronii bacteremia was associated with gastrointestinal symptoms, such as abdominal pain, presented by the patient. Sepsis caused by this bacterium is more frequent in immunocompromised patients, such as those with chronic liver disease, and is associated with a higher mortality rate.